2022
DOI: 10.1021/acssuschemeng.2c03132
|View full text |Cite
|
Sign up to set email alerts
|

Circular Process for Phosphoric Acid Plant Wastewater Facilitated by Selective Electrodialysis

Abstract: Phosphoric acid production generates large volumes of industrial wastewater that cannot be treated efficiently by existing processes because of its low pH and high precipitation potential. At present, the wastewater is generally stored in evaporation ponds that are prone to breaches, leakage, and flooding.We developed an alternative three-step process for the treatment of phosphoric acid wastewater including selective electrodialysis, reverse osmosis, and neutralization. Testing the process with synthetic wast… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Electrodialysis (ED), an electrically driven ion exchange membrane separation process, has been used for desalinating various types of water, such as seawater and brine, brackish water, and wastewater, and separating charged species such as metal ions from liquid streams . However, scaling due to the precipitation of inorganic minerals in the ED stack is one of the critical issues reducing the ED separation performance and hindering its wide applications. Previous studies found that the scaling on the membrane during ED could lead to the increase in membrane potential difference and overall stack resistance and the decrease in membrane conductivity and ion exchange capacity, , which eventually leads to the decrease in desalination efficiency (DE) and the increase in energy consumption during ED desalination.…”
Section: Introductionmentioning
confidence: 99%
“…Electrodialysis (ED), an electrically driven ion exchange membrane separation process, has been used for desalinating various types of water, such as seawater and brine, brackish water, and wastewater, and separating charged species such as metal ions from liquid streams . However, scaling due to the precipitation of inorganic minerals in the ED stack is one of the critical issues reducing the ED separation performance and hindering its wide applications. Previous studies found that the scaling on the membrane during ED could lead to the increase in membrane potential difference and overall stack resistance and the decrease in membrane conductivity and ion exchange capacity, , which eventually leads to the decrease in desalination efficiency (DE) and the increase in energy consumption during ED desalination.…”
Section: Introductionmentioning
confidence: 99%
“…Young students are often more attentive to visually stimulating reactions in chemistry, , and the opportunity to mix chemicals with their own hands contributes to future chemistry identity on career intention . Acid–base chemistry is a natural phenomenon present in everyday life that is also important in research settings, such as wastewater treatment, , fertilizers, catalysis, drug development and delivery. Additionally, pH indicators provide a direct visual portrayal of the concepts behind acids and bases. Thus, there is a unique opportunity to present acid–base chemistry in an exciting manner to help foster curiosity and drive young students to explore fundamental chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…The development of low-reagent membrane processes for recovery phosphates from various streams and returning them to production can solve this problem [ 34 , 35 ]. Moreover, electrodialysis has already established itself as a promising method for the extraction and simultaneous concentration of phosphates at the final stage of such circulation schemes [ 36 , 37 , 38 , 39 , 40 ]. Secondly, researchers who are engaged in applied aspects of the development of such electrodialysis processes report low current efficiency [ 36 , 41 ] and relatively high energy consumption [ 42 , 43 ], as well as lower limiting concentrations of phosphates [ 44 , 45 ] which are achieved at electrodialysis processing of phosphate-containing solutions compared to other substances, such as NaCl.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, electrodialysis has already established itself as a promising method for the extraction and simultaneous concentration of phosphates at the final stage of such circulation schemes [ 36 , 37 , 38 , 39 , 40 ]. Secondly, researchers who are engaged in applied aspects of the development of such electrodialysis processes report low current efficiency [ 36 , 41 ] and relatively high energy consumption [ 42 , 43 ], as well as lower limiting concentrations of phosphates [ 44 , 45 ] which are achieved at electrodialysis processing of phosphate-containing solutions compared to other substances, such as NaCl. For example, the recovery of chlorides and phosphates is 90% and 40%, respectively, if sweet whey demineralization using ED reaches 70% [ 46 ].…”
Section: Introductionmentioning
confidence: 99%